EVALUASI KUALITAS PELAYANAN TRANSPORTASI LAUT BERDASARKAN METODE SERVQUAL PADA RUTE TERNATE–TALIABU - Andi Arifah Pasri; Muhammad Taufiq Yuda Saputra; Abdul Gaus (JURNAL SIPIL SAINS, 2026)
Abstract Sea transportation plays a vital role in supporting connectivity among archipelagic regions, particularly on the Ternate–Taliabu route in North Maluku Province, Indonesia. Service quality is an essential factor in meeting passengers' expectations and improving user satisfaction. This study aims to evaluate the quality of sea transportation services, analyze the service gap between passengers' perceptions and expectations, and identify priority service dimensions for improvement using the Service Quality (SERVQUAL) method. A descriptive quantitative approach was employed by distributing questionnaires to 200 respondents, consisting of 100 passengers of KM Al Sudais 21 and 100 passengers of KM Sabuk Nusantara 76. The analysis covered 24 service attributes representing six service dimensions: safety, security, reliability, comfort, convenience, and equality, based on the Indonesian Minimum Service Standards for sea transportation. The findings reveal that all service attributes on both vessels have negative SERVQUAL gap scores, indicating that the services provided have not fully met passengers' expectations. KM Sabuk Nusantara 76 achieved a smaller average SERVQUAL gap (-0.37) than KM Al Sudais 21 (-0.47), indicating relatively better service quality. The largest service gap on both vessels was found in the availability of wheelchairs, while information-related services showed the smallest gap. The priority service dimensions requiring improvement include equality, comfort, reliability, and security, particularly regarding accessibility facilities for passengers with disabilities, schedule punctuality, cleanliness of onboard facilities, and passenger orderliness. The results demonstrate that the SERVQUAL method is an effective tool for evaluating sea transportation service quality and establishing priorities for continuous service improvement. Keywords: SERVQUAL, service quality, sea transportation, user satisfaction, Ternate–Taliabu.